Radio with images: an attempt to systematize the use of videos on radio station web pages - Lopez, Débora Cristina (Brazilian journalism research, 2012)
This article presents some results of the study “Periodismo radiofónico y convergencia: un estudio comparativo sobre la influencia de las tecnologías de la información y de la comunicación en emisoras brasileñas y españolas”. We start with the discussions on hypermedia radio followed by an analysis of the use of video on websites of the Brazilian radio stations Gaúcha and Guaiba and the Spanish stations Cadena SER and RTVE. Using content analysis methodology, we propose a classification of videos into institutional and journalistic categories that are each subdivided into: a) exclusive, b) supplemental (either meta-journalistic or journalistic) and c) overlay. We emphasize that the rating of the journalistic content was based on the Spanish stations’ production, since the Brazilian broadcasters did not use this content during the analyzed period.